Genomic sequencing identifies secondary findings in a cohort of parent study participants. (December 2018) - Thompson, Michelle; Finnila, Candice; Bowling, Kevin; Brothers, Kyle; Neu, Matthew; Amaral, Michelle; Hiatt, Susan; East, Kelly; Gray, David; Lawlor, James; Kelley, Whitley; Lose, Edward; et al.
Abstract Purpose Clinically relevant secondary variants were identified in parents enrolled with a child with developmental delay and intellectual disability. Methods Exome/genome sequencing and analysis of 789 "unaffected" parents was performed. Results Pathogenic/likely pathogenic variants were identified in 21 genes within 25 individuals (3.2%), with 11 (1.4%) participants harboring variation in a gene defined as clinically actionable by the American College of Medical Genetics and Genomics. These 25 individuals self-reported either relevant clinical diagnoses (5); relevant family history or symptoms (13); or no relevant family history, symptoms, or clinical diagnoses (7). A limited carrier screen was performed yielding 15 variants in 48 (6.1%) parents. Parents were also analyzed as mate pairs (n  = 365) to identify cases in which both parents were carriers for the same recessive disease, yielding three such cases (0.8%), two of which had children with the relevant recessive disease. Four participants had two findings (one carrier and one noncarrier variant). In total, 71 of the 789 enrolled parents (9.0%) received secondary findings. Conclusion We provide an overview of the rates and types of clinically relevant secondary findings, which may be useful in the design and implementation of research and clinical sequencing efforts to identify such findings.